A randomized, controlled comparison of a stannous-containing dentifrice for reducing gingival bleeding and balancing the oral microbiome relative to a positive control - He, Tao; Huang, Shi; Yue, Feng; Wang, Lijiang; Liu, Jiquan; Xu, Jian (American journal of dentistry, 2021)
To evaluate the effect of a stannous-containing fluoride dentifrice on gingival health and on the composition of the oral microbiome versus a positive control dentifrice over 2 weeks, in a population of healthy adults with self-reported sub-optimal oral health at baseline. This was a randomized, controlled, double-blind clinical study. 87 subjects with self-reported sub-optimal oral health at enrollment were randomized to brush twice daily with either an experimental dentifrice (n= 43) or a marketed positive control dentifrice (n= 43), both containing stannous chloride and 0.321% sodium fluoride. All subjects used a soft, manual toothbrush that was provided. The Mazza modification of gingival papillary bleeding Index (Mazza GI) was used to assess gingivitis at baseline and at Week 2. Supragingival plaque was collected for microbiome composition analyses at baseline, Week 1, and Week 2. 83 subjects completed the study. Baseline means were balanced between the treatment groups (P> 0.34). At Week 2, the positive control dentifrice demonstrated a 63.8% statistically significant (P< 0.0001) reduction relative to baseline for Mazza number of gingival bleeding sites. The experimental stannous containing dentifrice provided a comparable 63.5% gingival bleeding reduction versus baseline. There was no significant (P= 0.96) difference between the two dentifrices for either Mazza GI score or number of bleeding sites measured. The microbiome composition analysis at Week 1 found that 28 gingivitis-associated bacterial genera, including Porphyromonas, Tannerella, and Fusobacterium, were significantly inhibited in both dentifrice groups when compared to baseline, while the relative abundance of genera associated with oral health, such as Rothia, Streptococcus, Haemophilus, and Lautropia, was significantly elevated after treatment. These improvements in the oral ecosystem were sustained at Week 2. An experimental stannous-containing sodium fluoride dentifrice significantly reduced gingival bleeding comparable to a positive control, and both dentifrices promoted a shift in the oral microbiome towards those genera associated with oral health in a subject population with self-reported sub-optimal oral health at baseline.